ENHANCING CUSTOMERS’ ESG INVESTMENTS: KEY FACTORS SHAPING FINANCIAL ADVISORS’ RECOMMENDATIONS - PAOLA BONGINI; DORIANA CUCINELLI; MONICA ROSSOLINI (Journal of Financial Management, Markets and Institutions)
This research explores the factors that shape financial advisors’ intentions to recommend Environmental, Social, and Governance (ESG) financial products to their clients. To address this, a survey was conducted among financial advisors from a leading European bank. The study draws on Ajzen’s [(1985) From intentions to actions: A theory of planned behavior. In: Action Control, 11–39. Berlin, Heidelberg: Springer], augmenting its core constructs with additional variables that act as proxies for ESG-related themes. The findings reveal that, alongside factors such as prior experience, perceived behavioral control, and subjective norms, advisors’ self-assessed knowledge of ESG investments significantly boost their willingness to propose ESG products to their clients. These results highlight the critical role of enhancing advisors’ ESG expertise to encourage broader adoption of ESG financial instruments. This study adds to the ongoing discussion about the pivotal influence of financial advisors in promoting ESG investment strategies.